ISSUES OF CRIMINALITY AMONG WOMEN AND COUNTERMEASURES IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article analyzes the problems of crime among women in Uzbekistan and the fight against it. The study examines various types of criminal acts against women in the country, including domestic violence, economic crimes, and sexual assault. The article discusses the role of the state in combating crime, the effectiveness of legal measures, and existing problems in society and their solutions. The study also suggests ways to reduce crime among women and increase gender equality in society.